Efficacy and tolerability of GLP-1 agonists in patients with type 2 diabetes mellitus: an Indian perspective. (December 2014) - Dharmalingam, Mala
Glucagon like peptide-1 (GLP-1) agonists have been able to address the unmet needs of type 2 diabetes patients across the world. Indian patients with type 2 diabetes have also been able to benefit from effects of GLP-1 analogues to a more or less similar extent compared with patients from other parts of the world. As there is no nationwide data on use of GLP-1 agonists in India, we used the clinical data from different studies and compared them with the global data on GLP-1 analogues. The review is limited to only two approved GLP-1 analogues in India: exenatide and liraglutide. The efficacy of GLP-1 analogues, in terms of glycated haemoglobin (HbA1c), fasting plasma glucose (FPG) and postprandial glucose (PPG), is found to be similar in Indian patients compared with the global data. The other beneficial effects such as weight loss, incidence of hypoglycaemia were found to be on similar lines in the Indian setting. In a single-centre study, liraglutide reduced the dose of antihypertensive medications due to its effect on blood pressure. The gastrointestinal adverse effects such as nausea and vomiting were major adverse events, but these were transient and varied from one particular agent to another. Liraglutide is found to be superior in terms of compliance compared with exenatide in the Indian setting. Overall, the GLP-1 analogues have presented a treatment option that gives patient a benefit of glycaemic control, weight loss and very low incidence of hypoglycaemia, but the cost of the therapy presents a major barrier.